Pengaruh Ekstrak Daun Mimba (Azadirachta indica Juss) Terhadap Mortalitas Hama Kutu Kebul (Bemisia tabaci) - Sri Maharani; Yusmaidar Sepriani; Hilwa Walida (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
The impact of chemical pesticides in the long run can have side effects on the environment and human health. Neem leaf extract (Azadirachta indica juss) is an environmentally friendly solution in controlling kebul lice pests (Bemisia tabaci). This study aims to get an effect on the dose of neem leaf extract (Azadirachta indica juss) which has the potential to control whitefly infestation (Bemisia tabaci). This research was conducted using 4 treatments, in one treatment repeated 5 times with different doses. Each repetition contained 10 whitefly (Bemisia tabaci). The results showed that there was a significant effect on the administration of neem leaf extract (Azadirachta indica juss) in suppressing mortality of whitefly infestation (Bemisia tabaci). Neem leaf extract (Azadirachta indica juss) at a dose of 50 ml and 75 ml gives a good effect on whitefly (Bemisia tabaci) pests.The impact of chemical pesticides in the long run can have side effects on the environment and human health. Neem leaf extract (Azadirachta indica juss) is an environmentally friendly solution in controlling kebul lice pests (Bemisia tabaci). This study aims to get an effect on the dose of neem leaf extract (Azadirachta indica juss) which has the potential to control whitefly infestation (Bemisia tabaci). This research was conducted using 4 treatments, in one treatment repeated 5 times with different doses. Each repetition contained 10 whitefly (Bemisia tabaci). The results showed that there was a significant effect on the administration of neem leaf extract (Azadirachta indica juss) in suppressing mortality of whitefly infestation (Bemisia tabaci). Neem leaf extract (Azadirachta indica juss) at a dose of 50 ml and 75 ml gives a good effect on whitefly (Bemisia tabaci) pests.